Surfactant therapy in premature babies: SurE or InSurE. Issue 11 (19th August 2019) - Jena, Soumya R.; Bains, Harmesh S.; Pandita, Aakash; Verma, Anup; Gupta, Vishal; Kallem, Venkat R.; Abdullah, Mohammed; Kawdiya, Apurva; on behalf of SURE group,
Abstract: Background: Preterm infants with respiratory distress syndrome (RDS) requiring surfactant therapy have been traditionally receiving surfactant by intubation surfactant and extubation technique (InSurE), which comprises of tracheal intubation, surfactant administration, and extubation. However, more recently noninvasive methods like least invasive surfactant therapy or minimally invasive surfactant therapy have been reported to be successful. These methods, avoid intubation thus minimize airway trauma and avoid barotrauma. The primary aim of this randomized trial was to compare the need for mechanical ventilation (MV) between the administration of surfactant via a thin catheter during spontaneous breathing and the InSurE technique. Methods: Preterm infant's ≤34 weeks with RDS requiring continuous positive airway pressure (CPAP) within 6 hours of life were prospectively randomized to receive early surfactant either by SurE (surfactant without endotracheal tube intubation) or InSurE technique. The need for MV within the first 72 hours and other related outcomes were analyzed between the two groups. Results: One hundred seventy‐five infants in each group were analyzed. The need for MV in the first 72 hours of life was significantly lower in the SurE group compared to the InSurE group (19% vs 40%, P  < .01). Similarly, duration of oxygen therapy and hospital stay were significantly shorter in the SurE group. Furthermore, bronchopulmonary dysplasia (BPD) rate was significantly lower among the infants administered surfactant by the SurE technique. Conclusion: In preterm neonates with RDS who are stabilized on CPAP, the SurE technique for surfactant delivery results in the reduced need for MV and also may decrease the rate of BPD in some vulnerable subpopulations.